Climate change related policy environment in agriculture and food security in Nepal - Thakur, Shree Bhagavan (Journal of Agriculture and Environment, 2018)
Agriculture is the main stay of Nepal's economy. This provides about one-third of national GDP and two-third of national employment. Agriculture is highly vulnerable to climate change due to more marginal farmers with small landholding, limited irrigation, low income level, limited institutional capacity, and greater dependency on climate-sensitive natural resources. The adverse effect of climate change on agriculture impacts on farm revenue, employment, income and GDP. Policy formulation in agriculture and food security sector concerning to climate change has become an imperative for poverty reduction, livelihood improvement and economic development. Compliance with global and national agreement, review of existing policy will provide an essential foundation to policy makers, planners and development workers to reform process. This paper intended to find the strength and weaknesses of existing plans, policies, strategies, acts which will support stakeholders in agricultural development.